Natural Regeneration Potential of Tree Flora at Bangabandhu Sheikh Mujib Safari Park (Bsmsp), Dulahazara, Cox’s Bazar, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The aim of this study was to evaluate the natural regeneration status of tree flora at Bangabandhu Sheikh Mujib Safari Park (BSMSP) in Dulahazara, Cox’s Bazar. Six blocks were created within the safari park to explore regeneration potential. A total of 41 sample plots of 5m × 5m size, each centered in the middle of a 20m × 20m vegetation survey plot, was taken. In total, 835 seedlings representing 56 tree species under 29 families were recorded. Euphorbiaceae was the dominant family with 8 species followed by Myrtaceae (6 species) and Combretaceae (4 species). The highest Family Relative Density (FRD) was represented by Myrtaceae (26.95%) followed by Euphorbiaceae (16.05%) and Dipterocarpaceae (12.93%). Euphorbiaceae showed the maximum Family Relative Diversity Index FRDI (14.29%) followed by Myrtaceae (10.71%) and Combretaceae (7.14%). The highest Family Importance Value Index (FIVI) was observed in Myrtaceae (37.66%), whereas Euphorbiaceae and Dipterocarpaceae represented 30.33% and 18.29%, respectively. Species in the order of descending value of Importance Value Index (IVI) were Syzygium fruticosum (24.10), Aporosa wallichii (12.30), Dipterocarpus costatus (12.10), Dipterocarpus alatus (11.60) and Fernandoa adenophylla (11.60). The regeneration percentage of seed-originated individuals was 72%, whereas the rest 28% individuals were from coppices. The onset of safe guard and preserve trees with proper management could contribute conserving native gene pool contribution to ecotourism.J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 1-12